Analysis of Factors Related to Delivery Method in a Primiparous Mother - Diana Pefbrianti; Esti Yunitasari; Tiyas Kusumaningrum (Pediomaternal Nursing Journal, 2016)
Introduction : Delivery is a condition needs to be prepared by mother. Mother must know what to do in labor. Delivery isoften considered to be scary, because it’s long and painful process . Many woman prefer tohave Caesarean Section (CS) without medical indication. CS numbers at the private hospitals is around 15%. Thepurpose of this study was to analize the factors related with delivery method at Pelita Insani Hospital Martapura. Method:Cross Sectional design was used in this study. The population were all patient in maternity care room in 2nd and 3th floorPelita Insani Hospital Martapura. Sample provided using purposive sampling and there were 28 as respondents, takenaccording to inclusion criteria. Data was collected using questionnaire. Data then analyzed using Spearman’s rhotest with level of significany < 0,05. Result: Result showed that knowledge (p=0,013) correlated with delivery method,while other factors such readiness (p=0,051), beliefs (p=0,065), needs and desires (p=0,956) and support (0,185) showedno correlation. Discussion : Further studies could continues with other variable and instrument related to thisexperiment.